2020
DOI: 10.5539/elt.v13n4p1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Saudi Cadets’ Learning Motivation and Their Vocabulary Knowledge

Abstract: This paper is a report on the study of the relationship between foreign/second language (L2) motivation and vocabulary knowledge. The population of the study is the cadets of a military academy in Saudi Arabia who study English as a foreign language. The total number of participants is 195 Saudis. The author uses the L2 Motivational Self System to investigate the cadets’ L2 motivation and the vocabulary test “X-Lex” (Meara & Milton, 2003) to measure their vocabulary size (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The results showed that AVS, ASE (SS, CO and AC), LM (ITM and ISM), and English reading performance were positively correlated with each other. This was in line with findings of other studies (e.g., Ibrahim, 2016;Yancey, 2014;Alqahtani, 2020).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results showed that AVS, ASE (SS, CO and AC), LM (ITM and ISM), and English reading performance were positively correlated with each other. This was in line with findings of other studies (e.g., Ibrahim, 2016;Yancey, 2014;Alqahtani, 2020).…”
Section: Discussionsupporting
confidence: 94%
“…Students with high motivation for reading are more likely to invest more time and effort in reading and eventually realize an improvement in reading ability (Schaffner et al, 2013). Previous studies have revealed that there is a significant positive relationship between AVS and students' LM (Ma & Lin, 2015;Alqahtani, 2020). To be specific, students with higher AVS tend to display stronger LM, which can exert a positive effect on their English reading performance.…”
Section: Learning Motivationmentioning
confidence: 99%
“…More specifically, L2MSS in our study is unrelated to performance on an English test. There are other studies which have also failed to identify an association between L2MSS components and English proficiency (Moskovsky et al, 2016;Al-Hoorie, 2018) while Alqahtani (2020) failed to detect a significant relationship between L2MSS and vocabulary size. It is possible that L2MSS does not relate to important and relevant real-life outcomes, such as performance on an English test, although the failure to identify connections between L2MSS and English test performance in our study could be ascribed to the peculiarity of the Saudi context and the questionnaire issues stemming from this.…”
Section: Discussionmentioning
confidence: 99%
“…This is why further L2MSS studies need to include L2 proficiency variables, measured via valid and widely accepted language tests. Thompson and Erdil-Moody (2016) emphasized the need to perform exploratory factor analyses of L2MSS scales in different (Eusafzai, 2013;Moskovsky et al, 2016;Alqahtani, 2020), not all of them explored the factor structure of L2MSS. Furthermore, Moskovsky et al (2016) were only interested in the factor structure of two subscales (L2LE and ILEs).…”
Section: Research Gap and Contribution Of The Studymentioning
confidence: 99%
“…Various factors influence vocabulary competence, including language exposure, learning strategies, and learning environments. Alqahtani (2020) found that Saudi EFL learners with greater language exposure developed higher vocabulary competence, emphasizing the impact of language immersion. Alharbi (2021) highlighted the importance of employing effective vocabulary learning strategies, such as contextual guessing and word association, in enhancing vocabulary competence among Arab EFL learners.…”
Section: Vocabulary Competencementioning
confidence: 92%